Proprioceptive training and sports performance - Federici, A.; Zumbo, F.; Lucertini, F.; Marini, C. F. (Journal of Human Sport & Exercise, 2020)
One of the current trends in the field of sports training concerns the integration into training programs of exercises defined as "proprioceptive", which also include balance exercises, used to optimize performance, prevention or recovery from injuries. After introducing and describing the main characteristics of proprioceptive training in sports, the present review aims to set out and analyse the various flaws in this type of training as it is commonly practiced, in order to lay the groundwork for future improvements in proprioceptive training. Our research highlights that it is common practice to combine proprioceptive training with training on unstable surfaces, generally meaning the same for both situations. Such practices are indicative of the confusion surrounding the concepts of proprioception and balance. Indeed, until these two concepts and their respective performance benefits are clearly differentiated, it will be difficult to move beyond the controversy surrounding proprioceptive training and hence. to make advances in the field of proprioceptive training research. In conclusion, therefore, against the comforting theories that accompany the use of proprioceptive training in relation to the improvement of performance, unfortunately there is a literature that shows many variables not yet considered or treated in an approximate way.